Study on the Importance of Physical Training for Junior Female Handball Teams from Romania - Postelnicu M.G; Mihaila M.I (Editura Universitatii Transilvania din Brasov, 2022)
The aim of this study is to bring to the fore the importance of physical training in the youth segment. Starting from the idea that physical training has an essential role in the training process of athletes, we conducted a sociological survey based on a questionnaire. The questionnaire was distributed written and online to a number of 56 coaches and theorists from the Physical Education faculties specialized in handball. The research methods used during this study were: the method of analyzing specialized and interdisciplinary literature, the pedagogical observation method, the survey method, the statistical-mathematical method, the graphic method and the tabular method. The results highlighted the fact that the didactic strategies designed to plan the physical training represent a defining element in the training process of the athletes during their sports training.